2017
DOI: 10.1097/pai.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SIRT1 is Associated With Poor Outcomes in Patients With Ovarian Carcinoma

Abstract: Sirtuin 1 (SIRT1), originally identified as a longevity gene, regulates DNA repair and metabolism by deacetylating target proteins such as p53. SIRT1 plays a key role in the pathophysiology of metabolic diseases and neurodegenerative disorders, and is considered to protect against age-related diseases including cancer. In contrast, SIRT1 may be oncogenic because its overexpression has been detected in many cancers. The aim of the present study was to clarify the expression and the role of SIRT1 in ovarian carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Furthermore, SIRT1 expression level was associated with increased overall survival rate in SIRT1-positive serous carcinoma (43). A previous study demonstrated that SIRT1 was upregulated in EOC tissues compared with is expression in matched NATs (44). This study revealed that SIRT1 contributed to EOC cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, SIRT1 expression level was associated with increased overall survival rate in SIRT1-positive serous carcinoma (43). A previous study demonstrated that SIRT1 was upregulated in EOC tissues compared with is expression in matched NATs (44). This study revealed that SIRT1 contributed to EOC cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 81%
“…SIRT1 is over-expressed in a majority of ovarian cancers [13,14], implying a role of SIRTs in ovarian tumorigenesis. HighexpressionofSIRT1isalso associated with malignant transformation of human ovarian tissue [15] and with ovarian carcinoma with poor prognosis [16]. Therefore, SIRT1 inhibition appears to be a good strategy to overcome cancer drug resistance and improve therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a decline in energy metabolism may play an important role in activating the cell death pathway and dysregulation of pyruvate kinase M2 (PKM2), which favor both carcinogenesis and the Warburg effect [17]. Previous study demonstrated that SIRT1 overexpression is associated with poor outcome and chemo-resistance in ovarian cancer of epithelial origin over-expression, and one of the mechanisms may involve the dysregulation of energy metabolism and stress response [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, polycystic ovarian syndrome is associated with decreased expression of SIRT1 [17]. High expression of SIRT1 is associated with malignant transformation of human ovarian tissue [18] and with poor outcomes in patients with ovarian carcinoma [19]. Despite the potential usefulness of SIRTs for diagnostics of ovarian dysfunctions, SIRTs other than SIRT1 do not seem to have been studied from this viewpoint.…”
Section: The Use Of Sirts As Markers Of Ovarian Cell Statementioning
confidence: 99%
“…Furthermore, mTOR (like SIRTs) may mediate FSH action on ovarian cells; FSH affected mTOR in rat [38] and porcine [26] granulosa cells, while synthetic mTOR inhibitors prevented the stimulatory influence of FSH and induce the inhibitory effect of FSH on proliferation, apoptosis, and steroidogenesis in porcine granulosa cells [26]. Natural mTOR inhibitor (rapamycin) treatment promoted apoptosis in healthy porcine ovarian cells [13], suppressed follicular growth and maturation in rodents [19,32], and increased the risk of oligomenorrhea in humans [39]. Resveratrol, the other mTOR blocker and activator of SIRTs, was able to induce apoptosis/atresia in porcine ovarian follicles [13].…”
Section: The Use Of Mtor Regulators To Study Control and Treat Tmentioning
confidence: 99%